Analisis Pertumbuhan Ekonomi Tiap Kawasan Di Provinsi Jawa Tengah Tahun 2012-2024 - Effri Satrio Dewanto; Dyah Maya Nihayah (Jurnal Pendidikan Indonesia, 2025)
This study aims to examine the influence of the Human Development Index (HDI), the Open Unemployment Rate (OUR), and the Labor Force Participation Rate (LFPR) on economic growth in seven regions in Central Java Province during the period 2012 to 2024. This study uses a quantitative approach with a panel data regression analysis method. The results of the analysis indicate that the HDI variable mostly has a negative and significant influence on economic growth, except in the Barlingmascakeb region. Meanwhile, the OUR variable consistently shows a negative relationship, indicating that increasing open unemployment has an impact on slowing economic growth. On the other hand, the LFPR variable mostly has a positive influence, although it is only significant in two regions. These findings indicate a gap in economic growth between regions, so that the formulation of a more inclusive and equitable development strategy is needed in the Central Java Province region.